Penutupan Diastema Rahang Rahang Atas dengan Restorasi Porselen Veneer Labial Tidak Langsung - Aprianto, Dharma Satya; Mir, Andi Adytha; Delima, Anita Rosa; Arsista, Dede; Maulani, Chaerita (Jurnal Material Kedokteran Gigi, 2022)
Performing treatment for diastema closure of the maxillary anterior teeth is a challenge for dentists. They are required to do the best possible treatment and are faced with various treatment options, such as direct and indirect restorations. A 32-year-old female patient came to the dental clinic with complaints of a space of her front teeth. The patient wanted her teeth to be fixed. She wanted the space between her teeth to be closed. On clinical examination it was found that there was a diastema between 11 and 21 with vital and healthy condition without any caries lesion. We perform the gingivectomy on the gingival margin of 11 and made the porcelain labial veneer restorations. The gingivectomy was planned to obtain a more aesthetic and symmetrical margin compared to 21. The porcelain labial veneer restorations chosen to be inserted to the patient. The restorations have adapted well to the teeth and soft tissues. Porcelain labial veneer treatment as an indirect restoration is one of the options for the cases of diastema closure of the maxillary central incisors due to their good aesthetic appearance.